2004
DOI: 10.1109/tdmr.2004.840856
|View full text |Cite
|
Sign up to set email alerts
|

Interface Trap Generation and Hole Trapping Under NBTI and PBTI in Advanced CMOS Technology With a 2-nm Gate Oxide

Abstract: This paper gives an insight into the degradation mechanisms during negative and positive bias temperature instabilities in advanced CMOS technology with a 2-nm gate oxide. We focus on generated interface traps and oxide traps to distinguish their dependencies and effects on usual transistor parameters. negative bias temperature instability (NBTI) and positive bias temperature instability in both NMOS and PMOS have been compared and a possible explanation for all configurations has been suggested. Recovery and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(51 citation statements)
references
References 28 publications
3
46
1
Order By: Relevance
“…4) practically no hysteresis is introduced (no NBTI stress) and also the oxide trap contribution is reduced, consistent with the idea that these traps are due to a thermally activated tunneling mechanism [16] rather than elastic (and thus temperature-independent) hole tunneling [1].…”
Section: E Lower Temperaturesupporting
confidence: 77%
See 1 more Smart Citation
“…4) practically no hysteresis is introduced (no NBTI stress) and also the oxide trap contribution is reduced, consistent with the idea that these traps are due to a thermally activated tunneling mechanism [16] rather than elastic (and thus temperature-independent) hole tunneling [1].…”
Section: E Lower Temperaturesupporting
confidence: 77%
“…Experimental differentiation between oxide and interface states is extremely challenging due to the rapid recovery of the degradation setting in as soon as the stress is removed. In particular, it has been observed that when after NBTI stress the device is positively biased, a considerable part of the recoverable component is lost [1][2][3][4]. Until recently, this has been explained by the detrapping of holes [2,3], while interface states have been assumed to only change their occupancy but do not recover.…”
Section: Introductionmentioning
confidence: 99%
“…An overview of NBTI and other aging effects can be seen in [36]. NBTI may increase the theshold voltage (VTH) of the PMOS transistors subjected to negative gate to source bias due to high temperature stress conditions [37]- [38]. If the preferred start-up value of a cell is stored during a long time, the PMOS transistor with smaller VTH is turned on and its VTH may increase because of NBTI degradation.…”
Section: E Advantages For Countering Agingmentioning
confidence: 99%
“…However continuous push for smaller devices and interconnects has moved the technology closer to a point of unreliability where such design paradigm is not valid [9]- [11]. For example, at 90nm technology Negative Bias Temperature Instability (NBTI), where a PMOS device degrades continuously with voltage and temperature stress, had become a major reliability concern, [12]- [13]. At 45nm, the problem has exacerbated due to lower threshold voltage, and Positive Bias Temperature Instability (PBTI) for NMOS devices has been added to the list [12].…”
Section: Yieldmentioning
confidence: 99%